Microbial network structure, not plant and microbial community diversity, regulates multifunctionality under increased precipitation in a cold steppe - Yang, Xuechen; Song, Wenzheng; Yang, Xue; Yang, Tianxue; Bao, Wenqing; Wang, Chengliang; Li, Junqin; Zhong, Shangzhi; Jiang, Qi; Li, Lu-Jun; Sun, Wei (Frontiers in Microbiology, 2024)
It is known that the dynamics of multiple ecosystem functions (i.e., multifunctionality) are positively associated with microbial diversity and/or biodiversity. However, how the relationship between microbial species affect ecosystem multifunctionality remains unclear, especially in the case of changes in precipitation patterns. To explore the contribution of biodiversity and microbial co-occurrence network to multifunctionality, we used rainfall shelters to simulate precipitation enhancement in a cold steppe in Northeast China over two consecutive growing seasons. We showed that increased 50% precipitation profoundly reduced bacterial diversity and multidiversity, while interannual differences in precipitation did not shift microbial diversity, plant diversity, and multidiversity. Our analyses also revealed that increased annual precipitation significantly increased ecosystem, soil, nitrogen, and phosphorous cycle multifunctionality. Neither increased precipitation nor inter-annual differences in precipitation had significant effect on carbon cycle multifunctionality, probably due to the relatively short period (two years) of our experiment. The co-occurrence network of bacterial and fungal communities was the most dominant factor affecting multifunctionality, the numbers of negative interactions, but not positive interactions, were linked to multifunctionality. In particular, our results provided evidence that microbial network topological features are crucial for maintaining ecosystem functions in grassland ecosystem, which should be considered in related studies to accurately predict the responses of ecosystem multifunctionality to predicted changes in precipitation patterns.